Presence of doctors and obstetrician/gynecologists for patients with maternal complications in hospitals in six provinces of Indonesia. (27th February 2019) - Pedrana, Alisa; Tholandi, Maya; Qomariyah, Siti Nurul; Sethi, Reena; Hyre, Anne; Amelia, Dwirani; Suhowatsky, Stephanie; Ahmed, Saifuddin
Abstract: Objective: To describe doctors' and specialist physicians' availability to manage obstetric complications in hospitals in six provinces of Indonesia. Methods: Data from a nonrandomized, quasi‐experimental pre‐post evaluation study were used to describe the distribution of providers by each cadre of worker and assess the availability of doctors and obstetrician/gynecologists (ob/gyns) for consultations for women experiencing postpartum hemorrhage or pre‐eclampsia/eclampsia, disaggregated by hospital type, province, referral status, and by time of day of provider consultation. Results: Among hospitals that should have comprehensive emergency obstetric and newborn care (CEmONC) services available 24 hours a day, 7 days a week, many did not have a doctor available to manage obstetric complications as they presented, despite there being an average of seven ob/gyns and four doctors registered for service across all facilities. Slightly over 50% of obstetric emergency cases admitted with postpartum hemorrhage and severe pre‐eclampsia/eclampsia did not receive a consultation from an ob/gyn. Among the patients who received consultations, about 70% received consultations by phone or SMS. Conclusion: Findings from this study indicate that persistent issues of maldistribution of maternal and newborn specialists and high absence rates of both doctors and ob/gyns at CEmONC hospitals during obstetric emergencies undermines Indonesia's efforts to reduce high maternal mortality rates. Abstract : A study of the distribution of providers by each cadre of worker and the availability of doctors and obstetrician/gynecologists for consultations with women experiencing postpartum hemorrhage or pre‐eclampsia/eclampsia, disaggregated by hospital type, province, referral status, and time of day of provider consultation.